2022
DOI: 10.5603/gp.a2022.0069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inflammatory markers in threatened abortions and spontaneous abortions

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Ginekologia Polska" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…24 Similarly, another retrospective study of 39 pregnant women with missed abortion and 239 normal healthy pregnant women reported high serum NLR rates in favor of missed abortion, while no significant difference was found in serum PLR values. 25 The pregnant groups in both those studies differed from those in the present research, and it is unclear whether these increased serum NLR and PLR values cause miscarriage, or whether that elevation is a result of miscarriage, in other words, whether they represent a cause or an effect. A previous study of 60 pregnant women with threatened miscarriage, 60 aborting pregnant women, and 60 healthy pregnant individuals reported significantly higher serum NLR values in the women with threatened miscarriage than in the other two groups, while no difference was detected in serum PLR values between the groups.…”
Section: Gestational Age On Admission (Week)contrasting
confidence: 68%
See 1 more Smart Citation
“…24 Similarly, another retrospective study of 39 pregnant women with missed abortion and 239 normal healthy pregnant women reported high serum NLR rates in favor of missed abortion, while no significant difference was found in serum PLR values. 25 The pregnant groups in both those studies differed from those in the present research, and it is unclear whether these increased serum NLR and PLR values cause miscarriage, or whether that elevation is a result of miscarriage, in other words, whether they represent a cause or an effect. A previous study of 60 pregnant women with threatened miscarriage, 60 aborting pregnant women, and 60 healthy pregnant individuals reported significantly higher serum NLR values in the women with threatened miscarriage than in the other two groups, while no difference was detected in serum PLR values between the groups.…”
Section: Gestational Age On Admission (Week)contrasting
confidence: 68%
“…A study comparing 40 pregnant women with missed abortion and 40 healthy pregnant women reported significantly higher maternal serum NLR and PLR values in cases of missed abortion 24 . Similarly, another retrospective study of 39 pregnant women with missed abortion and 239 normal healthy pregnant women reported high serum NLR rates in favor of missed abortion, while no significant difference was found in serum PLR values 25 . The pregnant groups in both those studies differed from those in the present research, and it is unclear whether these increased serum NLR and PLR values cause miscarriage, or whether that elevation is a result of miscarriage, in other words, whether they represent a cause or an effect.…”
Section: Discussionmentioning
confidence: 96%